The Main Role of Locus of Control and Professional Ethics on Lecturer’s Performance (Indonesian Lecturer Empirical Study) - Kusuma, Aditya Halim Perdana; Rina, Rina; Syam, Andi Hendra (International Review of Management and Marketing, 2018)
As the professional staff of higher education institution, a lecturer is not only required to have competence but also to have proficiency in socialization in surrounding environment. Besides considered to be able to teach, a lecturer is literally required to learn and keep his professional ethics both inside and outside the campus. In order to fulfill them, the control of locus of control and professional ethics play the role. This research aims at analyzing the relationship of locus of control and professional ethics with lecturer’s performance. The object of this research is 42 management department lecturers of private campuses with religious ideology in Makassar and this research employs a multiple linear regression as its analysis method. The results of this research state that internal locus of control has significant influence (0.018), external locus of control has no significant influence (0.584) and professional ethics has significant influence (< 0.01) on lecturer’s performance. The R2 Value is 0.783 or 78.3%. Keywords: Locus of Control, Professional ethics, Lecturer’s Performance JEL Classification: O15 DOI: https://doi.org/10.32479/irmm.6884